Machining slight burr formed micro-channels with different moving trajectories of a pyramidal diamond tip. Issue 9 (June 2016) - Yan, Yongda; Xue, Bo; Hu, Zhenjiang; Wu, Dongze
Abstract In this study, a tip-based channel fabricating method on aluminum alloy material is studied using different tip moving trajectories. A three-sided pyramidal tip is driven by a three-axis piezoelectric actuator to do the movements of the circle, the sharp ellipse (major axis along the feeding direction), and the flat ellipse (minor axis along the feeding direction) revolutions are the three kinds of moving trajectories used for machining. In each revolution, due to the shapes of tip and moving trajectory, there would be two cutting edges participating in machining process. Under these three trajectories, the variations of uncut chip thickness and cutting rake angle with tip revolving and the cutting length of every edge in each tip revolution are different, which results in different sizes of chips and burrs formed. Effects of these three moving trajectories on the material removal are studied in detail. Through processing experiments, it was found that without any deburring method, the channel machined using the sharp ellipse trajectory has two edges with no burr formed and could obtain better bottom surface quality with a smaller feed rate, while channels machined using the other two both have burrs at the right side, which results from the accumulation of chips. Finally, to eliminate or reduce this chip accumulation further, a three-dimensional moving trajectory is designed as a deburring method and used to process channels. It was found that this deburring method plays a significant role on the circle trajectory, but it is ineffective on the flat ellipse trajectory.